Kondisi Geografis yang dapat Menyebabkan Fenomena Frostbite : Systematic Review - Salsabillah, Umi; Mawaddani, Nala; Anggraini, Dwi Putri; Algazali, Mohamad Assegaf; Fadillah, Muhammad Alif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to systematically review scientific journals that discuss the relationship between geographical conditions and the occurrence of frostbite. The method used is a Systematic Literature Review, structured according to the Preferred Reporting System for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and registered in PROSPERO (CRD42020136170). Primary data was collected from three scientific databases: PubMed, Science Direct, and Google Scholar. Articles meeting the criteria were analyzed, focusing on the geographical conditions of countries at risk for frostbite. Out of 226 identified studies, only 14 articles met the criteria for further analysis. The results show that countries with cold seasons, temperatures below 0°C, strong winds, and inadequate self-protection are at higher risk of frostbite. Frostbite commonly affects adults to the elderly who continue outdoor activities in cold conditions with insufficient body protection. In conclusion, geographical conditions play a crucial role in increasing frostbite risk. Low temperatures, extreme weather, and public awareness of self-protection are the main factors contributing to frostbite occurrences in various regions.